A general two-step chemical vapor deposition procedure to synthesize highly crystalline transition metal dichalcogenides: A case study of MoS2. (April 2016) - Shidpour, Reza; Vosoughi, Manouchehr; Maghsoudi, Hadi; Simchi, Abdolreza
Graphical abstract: Highlights: A safe method was developed to synthesis transition metal dichalcogenides flakes. MoS2 monolayer can be synthesized on powder ZnO and SiO2 supports via this method. Monolayer ZnO and ZnS would be made by this new precursor and air annealing. Abstract: A green and simple synthesis method based on a two-step chemical vapor deposition approach has been developed to synthesize transition metal dichalcogenides flakes. With non-toxic precursor such as transition metal oxides and elemental sulfur, large-area, strong photoluminescent and uniform MoS2 nanoflakes were produced at a relatively low growth temperature (650 °C). Controlling the layer number and morphology was achieved only by precursor concentration without any oxide impurity revealed by SEM, PL and Raman spectroscopy. This method can be used to make wide range of metal chalcogenides such as ZnS, SnS2, PtS2 and PdS2 .